2016
DOI: 10.1111/jhq.12074
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Medical Malpractice Payouts in Spain

Abstract: Patient safety and professional liability are major concerns worldwide. Despite the pervasive influence of catastrophic malpractice payouts, little is known about the specific characteristics and the overall relevance and characteristics of these payouts, especially outside U.S. borders. Five hundred fifty claims led to a payout among 2,236 claims from January 1, 2004 to December 31, 2010, in Catalonia (Spain). We analyzed data on patient, provider, and claim characteristics. Accordingly to our sample, Spanish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…20,21 Recent publications even link this increase to a rise in insurance premiums covering professional liability, 22 which would be justified by the increased number of claims and an increasing trend in the number of high, catastrophic (employing a term coined by other authors) compensation claims. 9,10 This situation could worsen if health-specific projects come to fruition, 14 which may reduce compensation for medical errors relating to sick patients but differentiate those relating to healthy patients, such as mother and foetus, and others within this specialty. In addition, the highest compensation awards are correlated with injured individuals of under one year of age, 9,10 which is also the case here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 Recent publications even link this increase to a rise in insurance premiums covering professional liability, 22 which would be justified by the increased number of claims and an increasing trend in the number of high, catastrophic (employing a term coined by other authors) compensation claims. 9,10 This situation could worsen if health-specific projects come to fruition, 14 which may reduce compensation for medical errors relating to sick patients but differentiate those relating to healthy patients, such as mother and foetus, and others within this specialty. In addition, the highest compensation awards are correlated with injured individuals of under one year of age, 9,10 which is also the case here.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 This situation could worsen if health-specific projects come to fruition, 14 which may reduce compensation for medical errors relating to sick patients but differentiate those relating to healthy patients, such as mother and foetus, and others within this specialty. In addition, the highest compensation awards are correlated with injured individuals of under one year of age, 9,10 which is also the case here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compensation rate various across different studies in different countries. For example, few studies in the USA confirmed that 25 to 65% of malpractice claims resulted in monetary compensation [6], and a study conducted in a large region in Spain confirmed a slightly lower rate of 25% [7]. A systematic literature on malpractice claim at primary care conducted by Wallace et al (2013) found that 31.9% of the claims made between 1985 and 2008 resulted in payment in the US, the payout rate on paediatric claims in a study in France was as high as 72% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Este y otros trabajos 16,20 , respaldan el hecho de que la obstetricia soporta las indemnizaciones más elevadas, y por tanto aquellas que superan el 1.000.000D , lo cual también ocurre en nuestro caso. El rango en nuestra muestra se situó entre 6.000D y 1.200.000D , frente a los 200.775D y 743.310,98D del trabajo referido 19 . Estas diferencias se justifican por que el rango temporal, 25 vs. 6 años, no es comparable, tampoco el número de condenas, 25 frente a 550, ni la vía judicial estudiada.…”
Section: Discussionunclassified